Multilayer winding rope to drum with method “Steps” - Фидровская, Наталья Николаевна; Варченко, Иван Сергеевич (Eastern-European Journal of Enterprise Technologies, 2011)
Shows a new way of multi-layer spooling of rope on the drum by the stairs. Describes the benefits of the new method